2023
DOI: 10.3390/f14101946
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and Visualizing Human Soundscape Perception in Large-Scale Urban Green Spaces: A Case Study of the Chengdu Outer Ring Ecological Zone

Yuting Yin,
Yuhan Shao,
Huilin Lu
et al.

Abstract: Human soundscape perceptions exist through the perceived environment rather than the physical environment itself and are determined not only by the acoustic environment but also by the visual environment and their interaction. However, these relationships have mainly been established at the individual level, which may impede the efficient delivery of human-oriented considerations in improving the quality of large-scale urban spaces. Using the Chengdu Outer Ring Ecological Zone as an example, this study aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…They found that respondents in forest-type temples preferred natural sounds, while respondents in urban-type temples preferred Buddhism-related man-made sounds. Yin et al predicted individual-scale soundscape perception in large-scale urban green spaces (UGSs) based on environmental visual, aural, and functional characteristics [12]. Prediction results suggested that people's perceived soundscape satisfaction increased as the distance from the ring road increased, and it gradually reached its highest level in the green spaces stretched outside the ring road.…”
Section: Summary Of Articles Included In the Special Issuementioning
confidence: 99%
“…They found that respondents in forest-type temples preferred natural sounds, while respondents in urban-type temples preferred Buddhism-related man-made sounds. Yin et al predicted individual-scale soundscape perception in large-scale urban green spaces (UGSs) based on environmental visual, aural, and functional characteristics [12]. Prediction results suggested that people's perceived soundscape satisfaction increased as the distance from the ring road increased, and it gradually reached its highest level in the green spaces stretched outside the ring road.…”
Section: Summary Of Articles Included In the Special Issuementioning
confidence: 99%